REAL EXCHANGE RATE AND ECONOMIC FUNDAMENTAL: EMPIRICAL STUDY OF ASEAN-5 - Didi Nuryadin (Economic Journal of Emerging Markets, 2009)
This paper studies the effect of fundamental economic variables on real exchange rates in Asean-5. The fundamental economic variables are capital mobility, technological progress, terms of trade, opennes index and fiscal policy. The paper applies panel unit root test, panel cointegration test, and Engle-Yoo three-step for short run and long run equilibrium. The result indicates that purchasing power parity holds in the short run. The estimation of equilibrium real exchange rate equation suggests that the direction of the coefficients is in accordance with the theory. It also finds that capital inflow negatively influences equilibrium real exchange rates, and that technological progress affects real exchange rate.